Financial literacy and environmental sustainability in SMEs: process innovation as an association mechanism - Molina-García, Antonio; Galache-Laza, María Teresa; González-García, Vicente; Diéguez-Soto, Julio (Springer Nature, 2025)
Despite receiving little attention in academia, understanding the factors that facilitate SMEs in becoming more environmentally responsible is a crucial challenge in today’s world. This article analyses the influence of CEOs’ financial literacy on environmental sustainability in an SME environment. Based on a random sample of 318 Spanish SMEs, our results show that CEOs’ financial literacy is an important driver of environmental sustainability. Moreover, this relationship emerges entirely through process innovation. Thus, CEOs who are financially literate are more engaged in process innovations, which facilitates them to embrace more environmentally sustainable practices. These findings offer fresh evidence of the relevance of CEOs’ capabilities in preserving natural resources.
Keywords: Educación; Finanzas; Pequeñas y medianas empresas; Economía social; Desarrollo sostenible; Financial literacy; Process innovation; Environmental sustainability; SMEs